EFEKTIFITAS KEBIJAKAN KURSUS CALON PENGANTIN DALAM PENGUATAN KELUARGA MUDA (Studi Pada Kantor Urusan Agama Kecamatan Ratu Samban Kota Bengkulu) - Fitri, Rahmi (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2018)
The study concluded that: first, the policy taken by the head  of the KUA Kecamatan Ratu  Samban suscatin services was related  to schedule  the execution of suscatin,  providing  a free service to any  of the participants suscatin,  implement  the suscatin for 2 hours with priority material pertaining  to marriage  and households only. Second, the implementation of suscatin in KUA Kecamatan Ratu   Samban held as much  as 2 times in a week, namely  on Thursday. Participants who follow suscatin at KUA Kecamatan Ratu  Samban average each  week 2 – 3 couples  or 8 – 12 pairs per month. The material  provided among others the procedures for marriage, wedding,  Fiqh rules on marriage  and the family, the rights and obligations of husband and wife and family concepts  of sakinah  is given by using the method of lecture and question and answer.  The bride gives a varied response associated with the Government’s policy to hold suscatin to every bride. Third, the evaluation of the implementation of the suscatin  in the Subdistrict  of Ratu   Samban KUA is already  well underway in accordance with the tasks and  functions primarily in the service of marriage  guidance to society. Implementation of the suscatin Sub-district office KUA Ratu  Samban quite effective and successful in adding  to the knowledge  and insight of the bride that will foster household. Suscatin be a posi- tive effort in provide  knowledge  to the prospective bride and  groom.  This is an attempt  to prevent  early on things which can disrupt home  life in order not to divorce occurs